Influence of Sacral Slope on the Loading of Pedicle Screws in Postoperative L5/S1 Isthmic Spondylolisthesis Patient: A Finite Element Analysis. Issue 23 (1st December 2016) - Chen, Liang; Feng, Yu; Che, Chun-Qing; Gu, Yong; Wang, Ling-Jun; Yang, Hui-Lin
Abstract : Study Design: A finite element analysis. Objective: To evaluate the influence of sacral slope (SS) on the loading of pedicle screws in postoperative isthmic spondylolisthesis (IS). Summary of Background Data: The spinopelvic anatomy was important for the biomechanics in spondylolisthesis. To our knowledge, no study concentrated on the postoperative biomechanics of the IS with the different SS. Methods: Based on the computed tomography images, a finite model of L5/S1 IS was constructed. Posterolateral fusion (PLF) and posterior lumbar interbody fusion (PLIF) models were simulated with different sacral slope (35°, 40°, 45°, 50°, and 55°). Moreover, 500N preload was imposed on the L5 superior endplate and 15 Nm was given to simulate flexion, extension, lateral flexion, and rotation of the body. The maximum stress on the instrumentation was recorded in different model with different sacral slope. Result: The model of the L5/S1 IS was verified to be valid. The maximum stress on the internal fixation system of each model was always at the posterior part of the sacral screw or connection point between screw and rod. Except for the SS of 35° in PLIF model, all the maximum stress occurred in flexion loading, which was 535.47 MPa for PLF and 339.49 MPa for PLIF with SS of 55°. The stress on the sacral screw of the PLF was higher than that of the PLIF model with same sacral slope, for example, 453.38 MPa for PLF, 282.64 MPa for PLIF under flexion with SS of 45°. With the increase of the SS, the maximum stress on the sacral screws increased in both the PLF and PLIF models. Conclusion: The maximum stress on the internal fixation system of the PLF and PLIF concentrated at the posterior part of sacral screw or the connection point between the screw and rod. With the same SS, the stress on the screw of PLF was higher than that of PLIF. PLIF may be a better choice for IS with a high SS. Level of Evidence: N/A